2005
DOI: 10.1038/ni1235
|View full text |Cite
|
Sign up to set email alerts
|

Immune evasion by a staphylococcal complement inhibitor that acts on C3 convertases

Abstract: The complement system is pivotal in host defense but also contributes to tissue injury in several diseases. The assembly of C3 convertases (C4b2a and C3bBb) is a prerequisite for complement activation. The convertases catalyze C3b deposition on activator surfaces. Here we describe the identification of staphylococcal complement inhibitor, an excreted 9.8-kilodalton protein that blocks human complement by specific interaction with C4b2a and C3bBb. Staphylococcal complement inhibitor bound and stabilized C3 conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
349
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(364 citation statements)
references
References 42 publications
3
349
1
3
Order By: Relevance
“…The functions of these exported proteins are unknown, but we speculate that at least some may be virulence factors because proteins exported from bacteria are often toxins or proteins that interfere with the immune system (Beuscher et al, 1995;Emody et al, 2003;Jongerius et al, 2007;Rooijakkers et al, 2005). Several genes involved in transfer of the plasmid were identified, supporting previous in vivo and in vitro observations of horizontal pQC transfer .…”
Section: Discussionsupporting
confidence: 80%
“…The functions of these exported proteins are unknown, but we speculate that at least some may be virulence factors because proteins exported from bacteria are often toxins or proteins that interfere with the immune system (Beuscher et al, 1995;Emody et al, 2003;Jongerius et al, 2007;Rooijakkers et al, 2005). Several genes involved in transfer of the plasmid were identified, supporting previous in vivo and in vitro observations of horizontal pQC transfer .…”
Section: Discussionsupporting
confidence: 80%
“…scn (staphylococcal complement inhibitor) encodes an inhibitor of complement formation that reduces phagocytosis by neutrophils. Rooijakkers et al (2005) showed that scn is human specific and does not affect cow, goat or sheep complement. chp (chemotaxis inhibitory protein) encodes a modulator of chemokine responses that prevents neutrophil chemotaxis and activation.…”
Section: Human (N535)mentioning
confidence: 99%
“…The increased prevalence of MRSA infections and corresponding rise in life-threatening syndromes have made it imperative to elucidate the mechanisms of pathogenesis for S. aureus. The interaction between S. aureus and the host is complex and is mediated by an array of bacterial proteins that both mediate the various pathologies and modify the immune system of the host (4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%